Understanding Customers / Second Edition - Rice Chris (Butterworth Heinemann, 1997)
Foreword, Preface, Identifying the Customer, Understanding Customer Behaviour, Investigating Customers, Predicting and Influencing Customer Behaviour, Index.
Foreword, Preface, Identifying the Customer, Understanding Customer Behaviour, Investigating Customers, Predicting and Influencing Customer Behaviour, Index.